Pelatihan teknik dasar dan pembuatan lapangan olahraga permainan petanque pada remaja Mesjid Nurul Huda di Kabupaten Takalar - Sudiadharma Sudiadharma; Suardi Suardi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Petanque sports games, one of the sport games that has recently been known in Indonesia. Petanque sports became known after the SEA Games 2011. Although since 2001 in Kuala Lumpur Malaysia, petanque games have been known in Southeast Asia, but later in 2011 petanque sports games were officially known in Indonesia after the implementation of the 2011 SEA Ganes. Where Indonesia is the host, and Indonesia must automatically include Petanque athletes in the SEA Games. At the 2011 SEA Games sporting event in Indonesia, Pétanque has become one of the competing sports. Typically other sports, petanque at SEA Games is included in the category of concentration sport, has certain prerequisites. This game is usually played on hard ground, but can also be played on grass, sand or other soil surface. To realize these efforts, it is necessary to have facilities and infrastructure for coaching towards achievement. Therefore coaching for adolescents is an important factor in enhancing the training and performance of petanque sports in South Sulawsei, especially in Takalar and its surroundings. The methods used are direct approach, demonstration, discussion, practice and evaluation of students' absorption and general in participating petanque sport with technique of throwing boule well. The target to be achieved in this training is to get petanque athletes capable of using techniques and able to play petanque well and correctly